Harnessing sediment voids of low-grade salt mines for compressed air energy storage: Experimental and theoretical insights - Li, Qihang; Liu, Wei; Jiang, Liangliang; Ju, Yiwen; Hassanpouryouzband, Aliakbar; Zhang, Guimin; Kong, Xiang-Zhao; Xu, Jun (International journal of mining science and technology, 2025)
Renewable energy storage technologies are critical for transitioning to sustainable energy systems, with salt caverns playing a significant role in large-scale solutions. In water-soluble mining of low-grade salt formations, insoluble impurities and interlayers detach during salt dissolution and accumulate as sediment at the cavern base, thereby reducing the storage capacity and economic viability of salt cavern gas storage (SCGS). This study investigates sediment formation mechanisms, void distribution, and voidage in the Huai’an low-grade salt mine, introducing a novel self-developed physical simulation device for two butted-well horizontal (TWH) caverns that replicates compressed air injection and brine discharge. Experiments comparing “one injection and one discharge” and “two injections and one discharge” modes revealed that (1) compressed air effectively displaces brine from sediment voids, (2) a 0.5 MPa injection pressure corresponds to a 10.3 MPa operational lower limit in practice, aligning with field data, and (3) sediment voidage is approximately 46%, validated via air-brine interface theory. The “two injections and one discharge” mode outperformed in both discharge volume and rate. Additionally, a mathematical model for brine displacement via compressed air was established. These results provide foundational insights for optimizing compressed air energy storage (CAES) in low-grade salt mines, advancing their role in renewable energy integration.